Eating their way to the top? Mechanisms underlying the success of invasive insect generalist predators - Crowder, David W; Snyder, William E (Biological invasions, 2010)
Insect generalist predators have been introduced outside of their native range intentionally to improve biological control, or accidentally during commerce, and can subsequently become invasive. Invasive insect generalist predators (IIGP) have widespread impacts on invaded communities because they consume both herbivores and other predators. Also, they often reach higher densities than and displace similar native species. Reflecting the complexity of their ecological roles, a wide variety of mechanisms might contribute to invasive success by IIGP. These species often drive resources to lower levels than do natives, leading to intense resource competition and sometimes competitive exclusion of other predators. The broader range of resources used by many IIGP can heighten their competitive advantage, particularly when IIGP exploit modified habitats. In either case, IIGP improve herbivore suppression by depressing prey densities below pre-invasion levels. Coexistence among native and invasive generalists is fostered when species differ substantially in their niche requirements. In this case, a larger proportion of the total prey population is subject to attack post- than pre-invasion, which strengthens prey suppression. On the other hand, some IIGP feed heavily on other predators, at times leading to a weakening of prey suppression. Future research should continue to explore the roles of competition and niche partitioning on larger spatial scales, and in both the native and invasive ranges of IIGP. Additionally, combining data from empirical studies with theory might be an effective way to predict the spread and community impacts of IIGP invasions.